Oscillatory kinetics at solid/solid phase boundaries in ionic crystals - Janek, Jürgen; Justus Liebig University Giessen (My University, 2000)
The transfer of matter and charge across interfaces between two solids is related to defect relaxation in the regions near the interface. A transfer rate which exceeds the rate of defect relaxation may lead to degradation of the interface, causing a feedback effect for the transfer process itself. As a consequence, non-linear phenomena (dissipative structures) like periodic oscillations of the interfacial properties can occur under conditions far from equilibrium. Possible mechanisms and experimental examples are discussed.
Keywords: Dissipative structures; Electrochemical oscillations; Interfaces; Ionic conductors; Point defects; ddc:540